Glioblastoma multiforme of the pineal region: case report - Emerson Leandro Gasparetto; Danny Warszawiak; Guilherme Pradi Adam; Luiz Fernando Bleggi-Torres; Arnolfo de Carvalho Neto (Arquivos de Neuro-Psiquiatria)
PURPOSE: pineal region tumors are uncommon, and comprise more frequently three categories: germ cell, parenchymal cell and glial tumors. Most pineal gliomas are low-grade astrocytomas. Glioblastoma multiforme, the most aggressive and common brain tumor, is extremely rare at this location with only few cases reported. CASE DESCRIPTION: a 29-year-old woman with a two month history of headache, nuchal pain, fever, nausea and seizures and physical examination showing nuchal rigidity, generalized hypotony, hypotrophy and hyper-reflexia, Babinski sign and left VI cranial par palsy. CT scan examination revealed a ill-defined hypodense lesion at the pineal region with heterogeneous contrast enhancement. MRI showed a lesion at the pineal region infiltrating the right thalamic region. The patient underwent a right craniotomy with partial resection of the mass. The histological examination of paraffin-embedded material defined the diagnosis of glioblastoma multiforme. Post-operative radiotherapy was indicated but the patient refused the treatment and died two months afterwards. CONCLUSION: in spite of its rarity at this location, glioblastoma multiforme should be considered in the differential diagnosis of aggressive lesions at the pineal region.